The role of digital marketing platform ( Facebook, Instagram, Twitter) on the success of Domino’s Pizza Bangladesh - Akhter, Khaleda (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.